Keabsahan Surat Kuasa Membebankan Hak Tanggungan Yang Dibuat Terhadap Agunan Yang Masih Terikat Hak Tanggungan Untuk Kreditor Lain - Gilang Wisudha (Jurnal Legal Reasoning, 2018)
In the practice of granting and taking over interbank credit facilities, it could be done through the binding of collateral in the form of mortgage right. That process starts with issuing the power of attorney to impose mortgage right upon an object of mortgage for the old creditor. The assumption arises that the owner of the collateral does not have authority to sign such power of attorney without the prior written consent from the old holder of mortgage right. Another assumption is that in the implementation of burdening mortgage right with the power of attorney to impose mortgage right upon an object of mortgage is not in accordance with the law or legal procedure. This study examines how is the validity of the power of attorney to impose mortgage right upon an object of mortgage which is still bound to the collateral of credit facility to other creditors, and what is the basis for notary or the land deed officer in making the power of attorney to impose mortgage right upon an object of mortgage which is still bound to the collateral of credit facility to other creditors. This study uses normative legal research method and based on secondary data. Information collected by interview to some law practitioners and experts would be used to support the secondary data. There are different opinions regarding the validity of the power of attorney to impose mortgage right upon an object of mortgage which is still bound to the collateral of credit facility to other creditors because, until now, there is no act or legal regulation that explicitly regulates the terms and procedures as the standard for such kind of power of attorney.